HISTORICAL STUDY OF THE SOVIET PERIOD AND THE PERIOD OF INDEPENDENCE OF THE AMUDARYA BRANCH IN 1917-1922 - Abdullaev, Anvar Atamuratovich (SCIENCE and SOCIETY, 2026)
At the end of the 19th century and the first quarter of the 20th century, Turkestan had a unique jurisdiction in the political-legal, social-administrative, and economic spheres, the population of the country was politically, economically, and spiritually dependent and kept under control, and the popular uprisings in the region were scientifically based as a political crisis of the metropolis.
Keywords: Turkestan; Soviet period; period of independence; international law; uprisings; emergency commission; Sharia and customs; Soviet judicial system; prosecutor's office; the rule of law; jurisprudence; people